Socio-psychological characteristics of combatants' resocialization process - Lomakin, G. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In this work were analyzed and considered socio-psychological features and main approaches to socialization in the modern society of people who took part in military actions; defined main directs of socio-psychological works with special category of citizens for more successful (re)adaptation in society of peaceful life.
Keywords: participants of the military actions; combat stress; psychic trauma; (re)adaptation; (re)socialization; rehabilitation